Reexamining the National Savings-Investment Nexus Across Time and Countries - David, Antonio (IMF Working Papers; Working Paper ;, 2020)
Domestic savings and investment are positively correlated across countries and through time, as Feldstein-Horioka (FH) unveiled 40 years ago. We argue that an interpretation of this correlation based on market failures is more consistent with data patterns than alternative hypotheses. Moreover, resorting to instrumental variables techniques, we conclude that the relationship is causal: an exogenous rise in savings increases investment. This result holds in the full sample of countries and for emerging and developing economies, but there is evidence that the positive association in advanced economies is due to endogeneity bias. The core of our identification strategy relies on the idea that population age structure influences savings, but not total investment directly. Specifically, we use the share of adults in the [35-49] years of age bracket as an instrument for savings. Our estimates pass weak-instruments robust inference.